Molecular Insights into Extracellular Polymeric Substances in Activated Sludge - Yu, Han-Qing (Environmental science & technology, 2020)
Extracellular polymeric substances (EPS) are known to crucially affect the properties and performance of activated sludge, but the detailed influential mechanisms and the pertinence to specific compositional, structural properties of EPS are still elusive. Such knowledge gaps have severely limited our ability in optimizing biological wastewater treatment processes, for which long-term robust and efficient sludge performance remains one of the main bottlenecks. Here, we overview the new knowledge on the molecular structure of sludge EPS gained over the past few years and discuss the future challenges and opportunities for further advancing EPS study and engineering. The structural and functional features of several macromolecules in sludge EPS and their important structural roles in granular sludge are analyzed in detail. The EPS–pollutant interactions and environment-dependent regulation machinery on EPS production are deciphered. Lastly, the remaining knowledge gaps are identified, and the future research needs that may lead to molecular-level understanding and precise engineering of sludge EPS are highlighted.